Parasitic castration by a viral protein tyrosine phosphatase targeting the host cell cycle checkpoint protein Rad9A - Hongshuai Gao; Mujuan Guo; Xin Yang; Rongmin Hu; Kun Wu; Lan Pang; Xiqian Ye; Jianhua Huang; Xuexin Chen; Zhizhi Wang (Proceedings of the National Academy of Sciences, 2026)
Parasitic castration is a widespread strategy where parasites hijack host reproductive resources, yet the key molecular mechanisms driving this phenomenon remain poorly understood. Here, we reported that parasitization by the parasitic wasp Cotesia vestalis triggers apoptosis-mediated castration in the larval testes of its lepidopteran host, Plutella xylotella . Such a phenomenon was mediated by CvBV_22-9 , a testis-enriched protein tyrosine phosphatase (PTP) encoded by Cotesia vestalis bracovirus (CvBV), a domesticated virus endogenized in the wasp. Similarly, a homolog of CvBV_22-9, encoded by the Microplitis manilae bracovirus, is involved in testis castration by inducing apoptosis in parasitized fall armyworm, Spodoptera frugiperda . Mechanistically, CvBV_22-9 binds to a cell cycle checkpoint protein, Rad9A, but does not alter its tyrosine phosphorylation level. Crucially, CRISPR-Cas9 knockout of Rad9A causes embryonic lethality and severe testis defects. Validation in Drosophila melanogaster shows that testis-specific expression of CvBV_22-9 or Rad9A knockdown induces apoptosis, while combined targeting synergistically enhances this effect, suggesting a conserved function of both proteins in insects. Our study uncovers a regulatory mechanism where a parasitoid wasp deploys a domesticated viral PTP that functions as a pseudophosphatase to induce Rad9A-mediated apoptosis and disrupt host testis development and spermatogenesis. This mechanism highlights a sophisticated strategy of host exploitation by parasitoid wasps, providing insights for the biocontrol of lepidopteran pests.